Can Concurrent Abnormalities in Free Light Chains and Immunoglobulin Concentrations Identify a Target Population for Immunoglobulin Trials in Sepsis?*. Issue 11 (November 2017) - Shankar-Hari, Manu; Singer, Mervyn; Spencer, Jo
Abstract : Objectives: Light chains κ and λ are immunoglobulin constituents but also circulate independently in blood as free light chains. We investigated whether a concomitant abnormality in free light chain and immunoglobulin levels could identify a high risk of death sepsis subpopulation to inform future IV immunoglobulin trials. We tested whether light chain allelic inclusion occurs in circulating B cells. Design: Prospective cohort study. Setting: Adult general ICUs. Patients: Adult sepsis patients without any documented immune comorbidity. Interventions: None. Measurements and Main Results: Serum total free light chain, immunoglobulin G, immunoglobulin A, and immunoglobulin M were measured on ICU days 1, 3, and 7. Population normal ranges defined normal and abnormal categories. Logistic regression models tested any independent relationship between high free light chain, immunoglobulins and hospital mortality. CD19 B-cell subsets expressing cell surface κ and λ were quantified by flow cytometry; their frequencies were compared against healthy subjects and correlation assessed against free light chain concentrations. On ICU day 1, high free light chain λ and high free light chain κ were seen in 46.5% and 75.3% of the study cohort ( n = 101). Low immunoglobulin levels were commonplace (45.5%) at ICU admission. ICU admission day free light chain and immunoglobulin concentrations were significantly correlated. Septic patients had significantly more CD19 B cells expressing both κ and λ compared with healthy controls (median [interquartile range] 4.1% [2.4–11.0] vs 1.3% [1.2–2.9], respectively; p = 0.0001); these correlated with free light chain concentrations. Conclusions: To our knowledge, abnormalities and associations of free light chain in critically ill adults with sepsis have not been previously reported. The additional prognostic value of free light chain λ and the significance of allelic inclusion in B cells in sepsis require further investigation. Abstract : Supplemental Digital Content is available in the text.